Enhancing Motivation To Support Organizational Commitment Of Global Human Resources - Case Study Of Sonatrach Company - Hebbaz, Nahed; Nessraoui, Douniazed (جامعة الوادي - University of Eloued, 2022)
The study aims to shed light on the extent of Sonatrach's interest as a global company that employs workers from the mother country and foreign workers from different countries of the world in motivating its workers of different nationalities in order to support their organizational commitment. To achieve the objectives of the study, it relied on the descriptive analytical approach to describe the study variables and analyze the relationships between them. It also relied on the hypothetical deductive approach to extract the most important results by testing the established hypotheses. The study found that there is a positive and strong relationship between the dimensions of motivation and organizational commitment in Sonatrach company .Salaries and compensation are among the most important dimensions of motivation in terms of affecting the organizational commitment of employees. Enabling global cloud HR platforms to plan incentive policies and make decisions about promotions or key positions has an important role in retaining the best managers and employees.
مقال
Keywords: Motivation ; organizational commitment ; global company ; human resources management.